1999
DOI: 10.1002/(sici)1097-0142(19990401)85:7<1470::aid-cncr7>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the value of serum chromogranin A or serum gastrin levels in the assessment of the presence, extent, or growth of gastrinomas

Abstract: BACKGROUND Serum chromogranin A levels (CgA) are reported by some authors to be of clinical utility for assessing the presence or absence of a pancreatic endocrine tumor and tumor extent or growth. The aim of the current study was to assess this finding and compare the results with those from serum gastrin determinations (FSG) in a large cohort of patients with gastrinomas. METHODS In 112 consecutive patients with the Zollinger–Ellison syndrome serum CgA and FSG levels were measured and correlated with disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 89 publications
(195 reference statements)
4
21
1
Order By: Relevance
“…Moreover, plasma CgA levels correlated significantly with urinary 5-HIAA levels in our patients with midgut carcinoids and with plasma gastrin levels in those with gastrinoma. Similar correlations have already been reported by Nobels et al (4,8,13,14). It has therefore been suggested that elevations in CgA levels in patients with Zollinger-Ellison syndrome may be due to hyperplasia of the gastric enterochromaffine-like cells caused by chronic hypergastrinemia (14).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, plasma CgA levels correlated significantly with urinary 5-HIAA levels in our patients with midgut carcinoids and with plasma gastrin levels in those with gastrinoma. Similar correlations have already been reported by Nobels et al (4,8,13,14). It has therefore been suggested that elevations in CgA levels in patients with Zollinger-Ellison syndrome may be due to hyperplasia of the gastric enterochromaffine-like cells caused by chronic hypergastrinemia (14).…”
Section: Discussionsupporting
confidence: 73%
“…However, our results do not support this interpretation as we found no correlation between CgA and gastrin plasma levels in patients with gastric carcinoid and hypergastrinemia due to chronic atrophic gastritis. Moreover, Goebel et al (13) demonstrated recently that gastrinoma resection significantly reduced CgA levels in patients with Zollinger-Ellison syndrome.…”
Section: Discussionmentioning
confidence: 95%
“…Chromogranin A was measured twice in the hypersecretors during the study, between 2002 and 2005. As reproducibility for both gastrin and CgA from day to day has been shown to be high, 6,18 only single samples were measured on each occasion. Serum CgA was measured by an immunochemiluminometric assay (ICMA) with a normal range of 6-39 ng ⁄ mL performed by Quest Diagnostics (San Juan Capistrano, CA, USA).…”
Section: Gastric Biopsiesmentioning
confidence: 99%
“…2,3 Various studies have examined the clinical value of measuring circulating CgA as a surrogate marker for screening, diagnosis, prognosis, treatment response 4 and disease progression of neuroendocrine tumors 2, 4-13 including gastrinoma. 4,6 In some cases, especially in CgA-rich pheochromocytomas, circulating levels reflect tumour mass. 7,10 However, CgA has been shown to be of little value in diagnosing CgA-poor neuroendocrine tumours such as parathyroid adenoma.…”
Section: Introductionmentioning
confidence: 99%
“…CgA is, however, considered to be the best general marker for neuroendocrine tumours, particularly the carcinoid group (Ö berg 1997(Ö berg , Tomossetti et al 2001. It is raised in pancreatic neuroendocrine tumours, where more than 92% of active gastrinomas have been shown to have elevated CgA (Goebel et al 1999), and also in more than 60% of patients with multiple endocrine neoplasia type 1(MEN-1) (Ö berg & Skogseid 1998). CgA is a large molecule and may be processed differently by different tumour cells.…”
Section: Biochemical Diagnosismentioning
confidence: 99%